Evaluation of Decision-to-Delivery Interval and Its Effect on Maternal and Neonatal Outcomes in Category-1 and Category-2 Emergency Caesarean Section Deliveries: A Systematic Review - Jimmy Sakti Nanda Berguna; Masyitoh Basabih (Universitas Muhammadiyah Yogyakarta, 2023)
Emergency cesarean section is a surgery delivery through the abdomen that must be carried out immediately within a decision-to-delivery interval (DDI) <30 minutes because it threatens the maternal and neonatal. This study prevents prolonged DDI response time for emergency cesarean section categories 1 and 2. This study aims to determine the causes of prolonged DDI for maternal and neonatal outcomes so that hospital management becomes standardized with the standard of care for emergency cesarean sections and the quality of care for patients increases. A literature search was conducted through four databases, SpringerLink, ScienceDirect, Google Scholar, and PubMed, using keywords that matched the clinical questions. Article selection was carried out based on exclusion and inclusion criteria. The selected literature was reviewed and assessed for validity, importance, and applicability based on the Oxford Center of Evidence-Based Medicine guidelines. Nineteen (19) studies examined category 1 or category 2 emergency cesarean sections from publications from 2018 to 2022. Of the 19 studies, only 3 achieved a response time of 30 minutes for emergency cesarean section category 1 and 75 minutes for category 2. However, 17 studies explained that DDI did not affect maternal and neonatal outcomes. Factors that influence not achieving the DDI target are the unavailability of operating rooms, anesthesiologists, pediatricians, and insufficient nurses. On the other hand, lack of special training, no standard emergency cesarean section service, and limited places and facilities impact maternal and neonatal outcomes.